Magnetic detection of corroded steel rebar: Reality and simulations. (March 2020) - Mosharafi, M.; Mahbaz, S.B.; Dusseault, M.B.; Vanheeghe, Ph
Abstract: Reinforced concrete (RC) is common throughout modern industrial and civil infrastructure. Adding steel reinforcing bars ("rebar") to concrete improves tensile strength, but if exposed to adverse environmental conditions, rebar may corrode and lead to a progressively deteriorating concrete condition. Several techniques exist for assessing rebar corrosion conditions. Inspection of RC structures based on the self-magnetic concept is a Non-Destructive Testing (NDT) method that helps to quantify the steel reinforcement condition. Corrosion quantification helps to manage the human and financial risks associated with RC structural failure, premature replacement, or inadequate repair. In this study, an intact rebar and one with general corrosion are scanned with a 3D laser scanner. The captured point clouds are imported as real geometries to finite-element software, where their self-magnetic behaviors are simulated under the effect of Earth's magnetic field. Significant differences are found between the self-magnetic behavior of the corroded and intact rebars. For instance, the Y component magnetic flux density values of the intact rebar have a sinuous trend with a period of about 10 mm, equal to the distance between the rebar corrugation peaks, but no harmonic trend can be detected in the rebar with general corrosion. Self-magnetic data of the corroded and intact rebars are recorded and assessed through experiments, and the test results correlate well with the simulation outcomes.